2018
DOI: 10.5195/emaj.2018.146
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Entrepreneurship and Manufacturing Firms’ Performance

Abstract: The study evaluates the effect of corporate entrepreneurship (measured by innovation, proactiveness, risk-taking, strategic renewal and corporate venturing) on the non-financial performance of manufacturing firms in Nigeria (measured by market share and employees satisfaction). The study employed survey research design, through the administration of structured questionnaire to management staff of eight manufacturing firms in Nigeria. The findings revealed that innovation, risk taking, proactiveness, strategic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Hanci-Donmez and Karacay (2019) argued that CE mediates the link between high-performance human resource practices and firm performance. Eze (2018) evaluated the effect of CE on non-financial performance of manufacturing firms in Nigeria and found that all parts of CE (innovation, venturing, strategic renewal, proactiveness and risk-taking) are important for improving firms' market share and employees' satisfaction. More information of some literature we reviewed above is listed in Table I.…”
Section: Corporate Entrepreneurship and Emerging Market Firms' Performancementioning
confidence: 99%
“…Hanci-Donmez and Karacay (2019) argued that CE mediates the link between high-performance human resource practices and firm performance. Eze (2018) evaluated the effect of CE on non-financial performance of manufacturing firms in Nigeria and found that all parts of CE (innovation, venturing, strategic renewal, proactiveness and risk-taking) are important for improving firms' market share and employees' satisfaction. More information of some literature we reviewed above is listed in Table I.…”
Section: Corporate Entrepreneurship and Emerging Market Firms' Performancementioning
confidence: 99%
“…Survey research design was adopted in this study to generalize the findings of the study from the sampled population. This research design has been used by previous studies such as Olajide (2019); Eze (2018). The population for the study was full time staff in big three food related producing firms and two beverages producing industry in Nigerian: Nestle Nigeria Plc, Nigerian Breweries Plc, Cadbury Nigeria Plc and International Breweries.…”
Section: Methodsmentioning
confidence: 99%
“…Özellikle yüksek karlılık ve gelişme ile güçlü bağlar mevcuttur sonucuna ulaşmışlardır. Eze (2018), Nijerya'da yapmış olduğu çalışmada göre tüm kurumsal girişimcilik alt boyutları tüm finansal olmayan firma performansı boyutlarını pozitif yönlü ve anlamlı bir şekilde etkilemektedir sonucuna ulaşmıştır. Ülkemizde Altuntaş ve Dönmez (2010), tarafından yapılan ve otel işletmelerinin irdelendiği çalışmaya göre; girişimcilik, yenilikçilik, risk alma, proaktiflik ve saldırgan rekabetçilik alt boyutları ile değerlendirilirken, örgütsel performans finansal performans ve finansal olmayan performans üzerinden değerlendirilmiştir.…”
Section: Girişimci Davranış Ve öRgütsel Performansunclassified
“…Daha önce yapılan çalışmalar ile örtüşen sonuçlara ulaşılmıştır. Zahra ve Garvis (2000), tarafından ABD'de faaliyet gösteren firmalar üzerinde yapılan çalışma, Nijerya'daki inşaat firmaları (Eze, 2018), Nijerya'daki hizmet sektörü işletmeleri (Oladimeji vd., 2019), Çanakkale bölgesindeki otel işletmeleri (Altuntaş ve Dönmez, 2010), savunma sanayi çalışanları (Çalışkan vd., 2011), Türkiye'de faaliyet gösteren turizm belgeli dört ve beş yıldızlı otel işletmeleri (Özer, 2011), Ankara'da faaliyet gösteren yazılım sektörü çalışanları (Çalışkan ve Akkoç, 2012) üzerinde yapılan çalışmalardaki bulgular ile benzer şekilde, girişimci davranışın örgütsel performansa anlamlı ve pozitif etkisi tespit edilmiştir.…”
Section: Tartişma Ve Sonuçunclassified